2018
DOI: 10.1536/ihj.17-475
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of a Simple Echocardiographic Parameter, the Right Ventricular Systolic to Diastolic Duration Ratio, in Patients with Advanced Heart Failure with Non-Ischemic Dilated Cardiomyopathy

Abstract: The prognostic value of the right ventricular (RV) systolic to diastolic duration ratio (S/D ratio) in patients with advanced heart failure is not clear.We enrolled 45 patients with DCM (40 ± 13 years, 33 male) who were admitted to our hospital for evaluation or treatment of heart failure. The RV systolic and diastolic durations were measured using continuous Doppler imaging of tricuspid regurgitation, and the RV S/D ratio was calculated. Cardiac events were defined as cardiac death or left ventricular assist … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…Although it is important to attempt a more accurate estimation of systolic PAP by DE, one of the important roles of DE is to screen for suspected PH. 22) The mean PAP reflects the steady component of pulmonary flow and the functional status of the pulmonary vascular resistance, whereas the systolic PAP is expected to encompass the pulsatile component of arterial load, including the characteristics of right ventricular ejection and the characteristics of the proximal elastic pulmonary arteries and wave reflections. 2,3,23) Several studies 24,25) suggested that changes in elasticity and pulsatile pressure are primarily due to an increase in mean PAP in PH.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is important to attempt a more accurate estimation of systolic PAP by DE, one of the important roles of DE is to screen for suspected PH. 22) The mean PAP reflects the steady component of pulmonary flow and the functional status of the pulmonary vascular resistance, whereas the systolic PAP is expected to encompass the pulsatile component of arterial load, including the characteristics of right ventricular ejection and the characteristics of the proximal elastic pulmonary arteries and wave reflections. 2,3,23) Several studies 24,25) suggested that changes in elasticity and pulsatile pressure are primarily due to an increase in mean PAP in PH.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Heart failure is mainly caused by hypertension, coronary heart disease, valvular heart disease, dilated cardiomyopathy, etc. [4][5][6][7][8] The development of depression is caused by negative thoughts, rumination, feelings of hopelessness about loss of health and independence, as well as an uncertain future. [9][10][11] These depressive symptoms can result in high morbidity and mortality and diminished self-care and health-related quality of life, and there is lack of effective treatment strategies to alleviate depressive symptoms for heart failure.…”
mentioning
confidence: 99%
“…Our findings are consistent with previous studies and offer a plausible explanation for the physiological mechanism that causes a prolonged systolic duration and shortened diastolic duration due to the degree of impaired ventricular function and decreased cardiac output. [20][21][22] The D/S could be a particularly effective indicator because it may monitor 5498 not only prolongation of isovolumic contraction and relaxation periods but also shortening of the diastole filling period. Although durations of systole and especially diastole are strongly affected by heart rate, the correlation between D/S and heart rate in the patients with CHF, and the result shows no significant correlation.…”
Section: Discussionmentioning
confidence: 99%